PERAN KOMITE NASIONAL UNTUK RAKYAT PALESTINA (KNRP) DALAM BANTUAN KEMANUSIAN UNTUK PENGUNGSI PALESTINA DI LEBANON TAHUN 2015 - Riyan Zulfikar Aris; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
KNRP organization (the National Committee for Palestinian People) is one of the vehicles participating in efforts to reduce the poverty, humanitarian assistance and help improve the life of the Palestinian people. These institutions make himself as mediator for Muslims and people of Indonesia to manifest solidarity in providing support and humanitarian aid for the Palestinians.This article aims to explain the help that is given KNRP to Palestinian refugees in Lebanon, the object of this study are Palestinian citizens who fled to Lebanon. The method used is a qualitative and quantitative research methods by collecting data through books, journals, official publications, and websites that are relevant and direct interviews with the parties involved in the research conducted. Further use Pluralist perspective and role theory advanced by Mochtar Mas'oed theory as well as the level of analysis used are Group (interest Group).KNRP field of humanitarian assistance to Palestinian refugees in the end a positive impact on public awareness of the world to help provide financial assistance to the Palestinian people are displaced in Lebanon and in other countries. It can be seen after KNRP provide relief assistance emerged from various countries such as Egypt, Turkey and several countries in Europe.Keywords: PIC, Refugees, Palestine.